2018
DOI: 10.3390/su10124824
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Power Plant Control Strategy Based on Fuzzy Extended State Observer and Predictive Control

Abstract: The control of an ultra-supercritical (USC) boiler–turbine power plant is critical in maintaining the safety of the sustainable power grid. However, it is challenging due to the internal nonlinearity, hard manipulation constraints, and widespread uncertainties. To this end, a fuzzy extended state observer (FESO)-based stable fuzzy predictive control (SFPC) approach is developed in this paper. First, the control difficulties of the USC boiler–turbine unit are analyzed. Then, based on a Takagi–Sugeno (T–S) fuzzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Since the predictive model is of high importance, the improvement on the robustness of the predictive model is helpful for wide-range operation. The predictive model is the plant given by Equation ( 6) modified by ADRC, in the form as G MP (s) given by Equation (16). It can be found that even at the medium/low-load conditions, for the proposed model compensation-based MPC, the settling time and overshooting are as good as them at high-load conditions.…”
Section: Simulations On the Lm2500 Gas Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…Since the predictive model is of high importance, the improvement on the robustness of the predictive model is helpful for wide-range operation. The predictive model is the plant given by Equation ( 6) modified by ADRC, in the form as G MP (s) given by Equation (16). It can be found that even at the medium/low-load conditions, for the proposed model compensation-based MPC, the settling time and overshooting are as good as them at high-load conditions.…”
Section: Simulations On the Lm2500 Gas Turbinementioning
confidence: 99%
“…The first category of such approaches is based on feedforward compensation. The disturbance observer (DOB) 13,14 or extended state observer (ESO) 15,16 is used to estimate the lumped disturbance and the feedforward control law is designed separately to compensate the effects of disturbance. The second category integrates the disturbance estimation into predictive model.…”
Section: Introductionmentioning
confidence: 99%
“…The method needs to get specific structural forms of disturbance, which may be applied to the compensation for a certain kind of disturbance [9]. Moreover, some scholars also proposed the design methods of fuzzy disturbance observer and neural network disturbance observer, which are difficult to realize in engineering practice [14], [15].…”
Section: Introductionmentioning
confidence: 99%